Analysis of trends in the use of modern fiscal instruments to ensure the effectiveness of tax evasion reduction mechanisms - Akhmedov Feruz Bakhodirovich (Genius Journals, 2024)
This article describes large-scale reforms aimed at creating favorable conditions for doing business in the tax and financial sectors, improving the investment climate and further strengthening the confidence of business circles in our republic in recent еars. At the same time, such areas as underground trade and public catering, road transport, housing construction and repair, the provision of personal services were studied, scientific and practical conclusions and proposals were formed on foreign experience and its application in our country.
Keywords: tax revenues; analysis; analysisefficiency